1966
DOI: 10.1128/jb.91.2.718-724.1966
|View full text |Cite
|
Sign up to set email alerts
|

Host-Parasite Relationships in Experimental Airborne Tuberculosis I. Preliminary Studies in BCG-Vaccinated and Nonvaccinated Animals

Abstract: Host-parasite relationships in experimental airborne tuberculosis. I. Preliminary studies in BCG-vaccinated and nonvaccinated animals. J. Bacteriol. 91:718-724. 1966.-Previous studies from this laboratory on immunogenicity and allergenicity of defatted mycobacterial vaccines involved subcutaneous challenge of guinea pigs and killing of the animals 6 weeks later to evaluate the amount of disease. This type of experiment has been discontinued in this laboratory in favor of an airborne challenge type of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 12 publications
3
41
0
Order By: Relevance
“…It needs to be noted that shortening the period of progressive Mtb growth by the equivalent of one Mtb doubling time (28 h) would enable a vaccine to reduce the level of stationary infection by ‫ف‬ 50%. The finding that the pathogen grew at the same rate in immunized and naive mice for the first 12-15 d of infection is in accordance with results obtained with guinea pigs (18) and mice (19). The reason for the exceptionally long delay in immunized, as well as naive, mice before anti-Mtb immunity is expressed in the lungs remains unknown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It needs to be noted that shortening the period of progressive Mtb growth by the equivalent of one Mtb doubling time (28 h) would enable a vaccine to reduce the level of stationary infection by ‫ف‬ 50%. The finding that the pathogen grew at the same rate in immunized and naive mice for the first 12-15 d of infection is in accordance with results obtained with guinea pigs (18) and mice (19). The reason for the exceptionally long delay in immunized, as well as naive, mice before anti-Mtb immunity is expressed in the lungs remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Because the ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and Ag85B 240-254 peptides are Class II (IA b ) presented, it is reasonable to conclude that the cells that made IFN-␥ in response to them were CD4 T cells. This was confirmed by the results of an Elispot assay performed with lung cell suspensions magnetically depleted of Ն 90% CD4 cells.…”
Section: Earlier Increase In the Number Of Mtb-specific Cd4 T Cells Imentioning
confidence: 99%
“…The levels of lung protection afforded mice against M. tuberculosis challenge infection by BCG vaccination as shown by this study are similar to those shown previously by others for mice (4) and guinea pigs (9). The common finding has been that vaccination enables the host to reduce the level of lung infection but not to resolve it.…”
supporting
confidence: 90%
“…Ribi et al confirmed these findings, adding that significant pulmonary protection, greater than that obtained with living BCG, was also achieved by intravenous injection of oil in water emulsions of mycobacterial cell walls (9,10). Smith et al found little difference in the response of BCG-vaccinated and unvaccinated mice to virulent human respiratory infection, although the numbers of bacilli recovered from lungs and spleens in immunized mice were smaller at certain intervals of time after infection (11).…”
Section: Discussionmentioning
confidence: 91%